Análise de sobrevivência de dentes permanentes reimplantados após avulsão traumática - Sylvia Cury Coste (2019)
Avulsion implies complete displacement of the tooth of its socket, with the immediate rupture of periodontal ligament fibers and of the neurovascular apical bundle. Tooth replantation is the treatment of choice for avulsion, but its prognosis is still unpredictable. The literature on this type of treatment presents great variation and subjectivity regarding the outcomes evaluated compromising the comparison of the results and overall conclusions. The present study aimed to evaluate the survival of permanent replanted teeth after avulsion as well as its determinants. Records from patients treated at CTD-FO-UFMG between 1994 and 2018 were analyzed to collect clinical and radiographic data regarding the management of the avulsed element, emergency and sequential treatment, and time elapsed from replantation until tooth loss/extraction. The sample consisted of 576 permanent teeth followed-up for a median period of 2.7 years (range from 6 days to 19.9 years). By the end of the follow-up period, a total of 141 (24.4%) replanted teeth were lost/extracted The Kaplan Meier Survival estimator with the Logrank test, together with a Cox regression model were used to estimate the survival curve of replanted teeth and to compare the effect of demographic and clinical factors on survival of replanted teeth. A survival rate of 50% was observed after a period of 5.5 years. The median survival period for immature teeth was 4.2 years and for teeth with complete root development was 5.5 years what represented an increase of 51.3% (p = 0.002) in the loss rate. The increase of one-year in the patient's age at the time of trauma, up to the age of 16 years, reduced the rate of loss of replanted teeth by approximately 15% (p <0.001). The storage of the avulsed tooth in milk decreased the rate of loss of replanted teeth by 56.4% (p = 0.015). The stage of root development, the increase of the patient's age at the time of trauma, up to the limit of 16 years and the tooth storage medium were significant prognostic factors of the survival rate of permanent teeth replanted after traumatic avulsion